2014
DOI: 10.1186/1471-2229-14-113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating contribution of ionic, osmotic and oxidative stress components towards salinity tolerance in barley

Abstract: BackgroundSalinity tolerance is a physiologically multi-faceted trait attributed to multiple mechanisms. Three barley (Hordeum vulgare) varieties contrasting in their salinity tolerance were used to assess the relative contribution of ionic, osmotic and oxidative stress components towards overall salinity stress tolerance in this species, both at the whole-plant and cellular levels. In addition, transcriptional changes in the gene expression profile were studied for key genes mediating plant ionic and oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(90 citation statements)
references
References 71 publications
(127 reference statements)
10
80
0
Order By: Relevance
“…Similar results were obtained for the Na + /H + antiporter gene NHX2. This is in accordance with earlier findings that NHXs could not be used to predict salinity stress tolerance in barley plants (Adem et al, 2014). In contrast to these genes, the expression level of another stress-related gene, WALI6 showed a marked increase not only in salt-stressed, but also in salt-acclimated plants.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained for the Na + /H + antiporter gene NHX2. This is in accordance with earlier findings that NHXs could not be used to predict salinity stress tolerance in barley plants (Adem et al, 2014). In contrast to these genes, the expression level of another stress-related gene, WALI6 showed a marked increase not only in salt-stressed, but also in salt-acclimated plants.…”
Section: Discussionsupporting
confidence: 92%
“…A study with three barley cultivars with contrasting salt tolerance looked at expression of five candidate genes mentioned above that are considered to be involved in cellular tissue tolerance (Adem et al 2014). The study confirmed that tissue tolerance was a dominating component of the overall plant responses to salinity.…”
Section: Genes Involved In Tissue Tolerance -Can These Provide a Molementioning
confidence: 80%
“…The NHX1 proteins may operate principally as K + rather than Na + exchangers (Bassil et al 2011;Barragan et al 2012), with their major role being the regulation of cytosolic K + or pH. Furthermore, transcriptional changes in NHX1 and NHX2 expression were not correlated with salt tolerance in three barley cultivars (Adem et al 2014), and overexpression of AtNHX1 in barley did not improve its salt tolerance (Adem et al 2015). This may be because these proteins are regulated post-translationally.…”
Section: Genes Involved In Tissue Tolerance -Can These Provide a Molementioning
confidence: 99%
“…4A,B,C,D). Increased K + content in the shoots of plants under salinity has been often considered as a tolerance trait (Adem et al, 2014;Hariadi et al, 2011). Polyploid natural accessions in Arabidopsis show higher K + content in leaves, characteristic that correlates with NaCl tolerance, and attribute to the importance of high cytolosolic K + to suppress activity of caspase-like proteolytic and endonucleolytic enzymes triggering PCD.…”
Section: Discussionmentioning
confidence: 99%